Heat and Mass Transfer - Advances in Science and Technology Applications 2019
DOI: 10.5772/intechopen.84889
|View full text |Cite
|
Sign up to set email alerts
|

Heat and Mass Transfer of Additive Manufacturing Processes for Metals

Abstract: Additive manufacturing (AM), a method in which a part is fabricated layer by layer from a digital design package, provides the potential to produce complex components at reduced cost and time. Many techniques (using many different names) have been developed to accomplish this via melting or solid-state joining. However, to date, only a handful can be used to produce metallic parts that fulfill the requirements of industrial applications. The thermal physics and weld pool behaviors in metal AM process have deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…When evaporation occurs in the keyhole melting mode, however, it is reported that recoil pressure becomes the principal driving force of the molten metal [21]. Figure 1 helps to illustrate the powder melting and solidi cation evolution process in L-PBF [22]. When the laser is turned on, the beam energy is absorbed by the powder layer and the powder melts, resulting in a depression area, associated with the recoil force, caused by the evaporation of material.…”
Section: Introductionmentioning
confidence: 99%
“…When evaporation occurs in the keyhole melting mode, however, it is reported that recoil pressure becomes the principal driving force of the molten metal [21]. Figure 1 helps to illustrate the powder melting and solidi cation evolution process in L-PBF [22]. When the laser is turned on, the beam energy is absorbed by the powder layer and the powder melts, resulting in a depression area, associated with the recoil force, caused by the evaporation of material.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in the product's shape, tension, quantity and material properties are significant because of the specific demands of the physical product [8]. Visual simulations for products under special conditions are used as initial tests on exploitation conditions using Elemental Analysis (EA) [9]- [11].…”
Section: Introductionmentioning
confidence: 99%